Marketing Strategy for Tourism Destination by Social Media Instagram in Dinas Pariwisata Kota Tangerang Selatan - Saputra, Vironika Agustin; Nugraha, Rizki Nurul (Westscience Press, 2024)
This research analyzes the tourism destination marketing strategy by Instagram social media in Dinas Pariwisata South Tangerang City. The urgency lies in the increasing influence of social media in promoting tourist destinations This study used descriptive qualitative method. The research was conducted at the South Tangerang City tourism office and six tourist destinations, using interviews, questionnaires, observations, and literature searches. The method applied is descriptive qualitative with the SOSTAC approach assisted by SWOT analysis. The research results show that the strategy is considered good, but the lack of content uploads and interaction with followers reduces its effectiveness. This strategy aims to introduce South Tangerang City as an attractive destination on Instagram. It is hoped that the results of this study will provide insights for tourism marketing practitioners to enhance destination promotion strategies through social media.